2011
DOI: 10.1111/j.1745-4565.2010.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

OCCURRENCE, VIRULENCE GENES AND ANTIMICROBIAL RESISTANCE OF ESCHERICHIA COLI O157 IN BOVINE, CAPRINE, OVINE AND PORCINE CARCASSES IN GREECE

Abstract: One thousand and two hundred carcasses (620 bovine, 130 caprine, 230 ovine and 220 porcine) from several slaughterhouses throughout Greece were examined for the presence of Escherichia coli O157 after evisceration and before chilling. Twelve E. coli O157 strains (1.0%) were isolated of which eight were from bovine (1.3%), one from caprine (0.8%) and three from ovine (1.3%) meat. None was isolated from pork meat. Six out of the 12 E. coli O157 isolates (50.0%) could be classified as Shiga‐toxigenic based on pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In addition, 4.4% occurrence was reported in Kenya [ 31 ]. These variations might be due to different sampling techniques, areas, and time and lack of strict hygienic measures among the farms and cross contamination with other principal reservoirs [ 24 ] and also due to the low isolation rate of culture methods compared to more sensitive immunological and molecular methods [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 4.4% occurrence was reported in Kenya [ 31 ]. These variations might be due to different sampling techniques, areas, and time and lack of strict hygienic measures among the farms and cross contamination with other principal reservoirs [ 24 ] and also due to the low isolation rate of culture methods compared to more sensitive immunological and molecular methods [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lower carcass contamination might be due to low fecal prevalence of E. coli O157:H7 in these animals and operational activities in the slaughter house, which results in relatively low risk of contamination and cross contamination [5]. The exact contamination rate may be higher than the stated one due to the low isolation rate of culture methods compared to immunological and molecular methods [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed an increasing antibiotic resistance of E. coli O157 and O157:H7 in animals and meat (Magwira et al 2005;Govaris et al 2011). The presence of antibioticresistant strains in meat may represent a threat to human health because such strains can be transmitted to reach humans through the consumption of contaminated meat.…”
Section: Introductionmentioning
confidence: 99%